Conflicting logics of online higher education. Issue 5 (3rd July 2020) - Ivancheva, Mariya P.; Swartz, Rebecca; Morris, Neil P.; Walji, Sukaina; Swinnerton, Bronwen J.; Coop, Taryn; Czerniewicz, Laura
Abstract: The advent of massive open online courses and online degrees offered via digital platforms has occurred in a climate of austerity. Public universities worldwide face challenges to expand their educational reach, while competing in international rankings, raising fees and generating third-stream income. Online forms of unbundled provision offering smaller flexible low-cost curricular units have promised to disrupt this system. Yet do these forms challenge existing hierarchies in higher education and the market logic that puts pressure on universities and public institutions at large in the neoliberal era? Based on fieldwork in South Africa, this article explores the perceptions of senior managers of public universities and of online programme management companies. Analysing their considerations around unbundled provision, we discuss two conflicting logics of higher education that actors in structurally different positions and in historically divergent institutions use to justify their involvement in public–private partnerships: the logic of capital and the logic of social relevance.